A Comprehensive Inverter-BESS Primary Control for AC Microgrids - Michele Fusero; Andrew Tuckey; Alessandro Rosini; Pietro Serra; Renato Procopio; Andrea Bonfiglio (Energies, 2019)
This paper proposes the design of a comprehensive inverter-BESS primary control capable of providing satisfactory performances both in grid-connected and islanded configurations as required by international standards and grid codes, such as IEEE Std. 1547. Such control guarantees smooth and fast dynamic behavior of the converter in islanded configuration as well as fast power control and voltage-frequency support in grid-connected mode. The performances of the proposed primary control are assessed by means of EMT (ElectroMagnetic Transients) simulations in the dedicated software DIgSILENT PowerFactory® (Germany, Gomaringen) . The simulation results show that the proposed BESS (Battery Energy Storage System) primary control is able to regulate frequency and voltage in Grid-Forming mode independently of the number of paralleled generators. This is achieved adopting a virtual generator technique which presents several advantages compared to the conventional one. Moreover, the proposed control can be switched to Grid-Support mode in order to provide fast control actions to allow frequency and voltage support as well as power control following the reference signals from the secondary level.